Pleurothallis moniquirensis (Orchidaceae, Pleurothallidinae): A new species from the Eastern Andes of Colombia threatened by habitat loss, illegal collection, and mining - Sierra-Ariza, Mario Alexei; Wilson, Mark; Edwards, David P.; Perilla, German Beltrán; Parra-Sánchez, Edicson (Phytotaxa, 2025)
A new species of the genus Pleurothallis, discovered in the department of Boyacá, in the Eastern Andes of Colombia, is presented and illustrated. This species shows morphological similarities with Pleurothallis petroana; however, it differs in its oblong dorsal sepal; narrowly ovate, convex synsepal with strongly revolute margins; and lanceolate lip that is verrucose-papillose. In addition to its taxonomic description, its morphological affinities are discussed, and notes on its ecology and conservation status are provided. Our fieldwork data provide strong evidence to categorize the new species as Endangered under criteria B1ab(v)+B2ab(v) + C2a(i) due to its restricted distribution, commercial use in the local market, and the potential threat to its species range due to the establishment of a mine, and the high level of habitat loss around its occurrence.